Surgical or Radiation Therapy for the Treatment of Cervical Spine Metastases: Results From the Epidemiology, Process, and Outcomes of Spine Oncology (EPOSO) Cohort. Issue 1 (February 2020) - Bond, Michael R.; Versteeg, Anne L.; Sahgal, Arjun; Rhines, Laurence D.; Sciubba, Daniel M.; Schuster, James M.; Weber, Michael H.; Fehlings, Michael G.; Lazary, Aron; Clarke, Michelle J.; Boriani, Stefano; Bettegowda, Chetan; et al.
Study Design: Ambispective cohort study design. Objectives: Cervical spine metastases have distinct clinical considerations. The aim of this study was to determine the impact of surgical intervention (± radiotherapy) or radiotherapy alone on health-related quality of life (HRQOL) outcomes in patients treated for cervical metastatic spine tumours. Methods: Patients treated with surgery and/or radiotherapy for cervical spine metastases were identified from the Epidemiology, Process, and Outcomes of Spine Oncology (EPOSO) international multicentre prospective observational study. Demographic, diagnostic, treatment, and HRQOL (numerical rating scale [NRS] pain, EQ-5D (3L), SF-36v2, and SOSGOQ) measures were prospectively collected at baseline, 6 weeks, 3 months, and 6 months postintervention. Results: Fifty-five patients treated for cervical metastases were identified: 38 underwent surgery ± radiation and 17 received radiation alone. Surgically treated patients had higher mean spinal instability neoplastic scores compared with the radiation-alone group (13.0 vs 8.0, P < .001) and higher NRS pain scores and lower HRQOL scores compared to the radiation alone group ( P < .05). From baseline to 6 months posttreatment, surgically treated patients demonstrated statistically significant improvements in NRS pain, EQ-5D (5L), and SOSGOQ2.0 scores compared with nonsignificant improvements in the radiotherapy alone group. Conclusions: Surgically treated cervical metastases patients presented with higher levels of instability, worse baseline pain and HRQOL scores compared with patients who underwent radiotherapy alone. Significant improvements in pain and HRQOL were noted for those patients who received surgical intervention. Limited or no improvements were found in those treated with radiotherapy alone.